The Essentiality of Teacher Supervision as a Positive Cultural Driver in Creating Effective Schools at SDN Ciwangi, Purwakarta Regency - Rendra Bagus Cahyono; Elis Haryati; Dinny Mardiana; Suharyanto H Soro (Global Education Journal, 2025)
Effective schools play an important role in the implementation of quality education that supports a conducive, characterful, participatory and sustainable school climate. One of the strategic factors in realizing an effective school is the supervision carried out by teachers as agents of change in schools. Although many effective schools are found in Indonesia, the realization is that there are still shortcomings in the supervision process, namely administrative, fragmentary, lack of collaboration, and low motivation for teachers to become positive cultural drivers. This research uses a qualitative approach with case studies. The selection of case studies aims to gain a deep and comprehensive understanding of the essentiality of teacher supervision as a positive cultural driver in creating effective schools. The research was carried out at SDN Ciwangi, Purwakarta Regency. Data collection techniques through observation, interviews and document studies. The subjects of the study were determined through purposive sampling , namely 1 principal as the key informant, 5 teachers as the main informant, and 12 students as supporting informants from the impact of supervision. Structured and participatory supervision planning with the preparation of integrated supervision guidelines in school programs. The implementation of supervision is carried out in a collaborative and structured manner by directly observing student behavior in both intracurricular, cocurricular, extracurricular, and school culture processes. The evaluation process is carried out in a participatory and continuous manner through regular school meetings, the school's internal learning community, and parental feedback through google forms. Follow-up activities by selecting and sorting out indicators that have been achieved well and those that have not been used to improve teacher supervision strategies so that effective schools are created. Conclusion: Teacher supervision that drives positive culture is proven to support the creation of effective schools through planned, structured, participatory and sustainable supervision management